The mycobiome as integral part of the gut microbiome: crucial role of symbiotic fungi in health and disease - Hui Huang; Qiurong Wang; Ying Yang; Wei Zhong; Feng He; Jun Li (Gut Microbes)
The gut mycobiome significantly affects host health and immunity. However, most studies have focused on symbiotic bacteria in the gut microbiome, whereas less attention has been given to symbiotic fungi. Although fungi constitute only 0.01%–0.1% of the gut microbiome, their larger size and unique immunoregulatory functions make them significant. Factors like diet, antimicrobials use, and age can disrupt the fungal community, leading to dysbiosis. Fungal-bacterial-host immune interactions are critical in maintaining gut homeostasis, with fungi playing a role in mediating immune responses such as Th17 cell activation. This review highlights methods for studying gut fungi, the composition and influencing factors of the gut mycobiome, and its potential in therapeutic interventions for intestinal and hepatic diseases. We aim to provide new insights into the underexplored role of gut fungi in human health.